2019
DOI: 10.1111/acer.14213
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorders in a Pacific Southwest City: Maternal and Child Characteristics

Abstract: Background: There are limited data on the characteristics of children with fetal alcohol spectrum disorders (FASD) and their mothers from the general population in the United States.Methods: During the 2012 and 2013 academic years, first-grade children in a large urban Pacific Southwest city were invited to participate in a study to estimate the prevalence of FASD. Children who screened positive on weight, height, or head circumference ≤25th centile or on parental report of developmental concerns were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Since alcohol consumption can aggravate nutrient deficiencies, it has been suggested that maternal nutritional status plays a role in the risk for FASD (3)(4)(5). In addition, rates of cigarette smoking during pregnancy are often higher among women who consume alcohol creating additional consequences to nutritional status, as well as increasing odd ratios for preterm birth, low birth weight, and growth restriction beyond either alcohol or cigarette use alone (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Since alcohol consumption can aggravate nutrient deficiencies, it has been suggested that maternal nutritional status plays a role in the risk for FASD (3)(4)(5). In addition, rates of cigarette smoking during pregnancy are often higher among women who consume alcohol creating additional consequences to nutritional status, as well as increasing odd ratios for preterm birth, low birth weight, and growth restriction beyond either alcohol or cigarette use alone (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Alcoholism: Clinical and Experimental Research, 3 additional papers examining the prevalence of fetal alcohol spectrum disorders (FASDs; May et al, 2020a, 2020b, 2020c) follow the earlier paper by Chambers and colleagues (2019). These studies present state‐of‐the‐art FASD active case ascertainment (ACA) of prevalence among school‐age children conducted in the United States and demonstrate the importance of the behind‐the‐scenes intensive fieldwork necessary to complete studies of this size in community settings.…”
mentioning
confidence: 99%
“…The data also improve our understanding of the lower threshold of teratogenic exposure, which increases the risk for FASD. Chambers and colleagues have found the threshold to be very low, showing 1 drink per drinking day during pregnancy to increase the risk of FASD by over 3‐fold (Chambers et al, 2019).…”
mentioning
confidence: 99%
“…Another systematic review estimated that FASD affects 7.7 per 1,000 children and youth in the general population (Lange et al, 2017). More recently, a series of studies involving a large sample size examining the prevalence of FASD among school‐age children in 4 regions of the Unites States (Rocky Mountain, Midwestern, Southeastern, and Pacific Southwestern) has confirmed that at least 2% of children in first grade had FASD (Chambers et al, 2019; May et al, 2018, 2020a, 2020b, 2020c; Popova et al, 2020). The burden of FASD on society is a severe global medical issue (Lange et al, 2018).…”
mentioning
confidence: 98%